SYNTACTIC FRAMING: A CONTRASTIVE ECOLINGUISTIC STUDY OF ENGLISH AND INDONESIAN ECO-FRIENDLY ADVERTISEMENTS - Arkin (Vol. 3 No. 1 (2025): Proceeding of International Conference on Cultures & Languages 2025, 2025)
This study explores the syntactic framing strategies used in eco-friendly product advertisements by multinational brands in both English and Indonesian. Grounded in Leech’s syntactic theory and Stibbe’s ecolinguistic approach, the analysis focuses on grammatical features such as passive voice, nominalization, modality, purpose clauses, evaluative lexis, and thematic fronting to understand how environmental meanings are constructed. Data were collected from social media advertisements of brands including Unilever, Nestlé, Garnier, P&G, and Coca-Cola. The analysis shows that syntactic choices are used to emphasize ecological responsibility while often backgrounding corporate agency. This study introduces syntactic framing as the use of grammatical structure to influence perceptions of responsibility, agency, and environmental value. From the data, a typology of seven syntactic frames is identified including Heroic, Green Utopia, Harmony with Nature, Technological Fix, Individual Responsibility, Obfuscation, and Displacement. The comparison reveals that English advertisements tend to promote assertive agency and innovation, while Indonesian versions highlight moral responsibility and collective action. These findings demonstrate that syntactic structures play a crucial role in shaping green marketing discourse and offer a contribution to ecolinguistic research by linking grammar with environmental ideology.